Analisis Rencana Pelaksanaan Pembelajaran Berbasis High Order Thingking Skill Kelas Tinggi di Sekolah Dasar - Fika Dwi Maratusolekhah; Intan Rahmawati; Diana Endah Handayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
21st century in education demands that every classroom learning must be based on HOTS which can be applied to teacher learning tools such as lesson plans. HOTS-based learning can be integrated into the curriculum, one of which is in science learning, with the aim of finding out how the results of HOTS-based learning tools are in the form of making and implementing HOTS in the implementation of science learning for class IV odd semesters at SDN Bugangan 01 Semarang. This type of research is descriptive qualitative research. The subject of this research is the fourth grade teacher. The data in this study were obtained through interviews, observation and documentation. Findings Based on the overall discussion and discussion, it proves that the teacher has implemented HOTS in the lesson plans, made in accordance with the standards for preparing curriculum learning tools. However, there are still some parts of the preparation of the lesson plans that must be improved because they are not in accordance with the guidelines for preparing the correct lesson plans but overall they are good.